(6) سياسات واليات تعميق الصناعات الالكترونية في مصر في ضوء الخبرات الدولية وتقييم الممارسات المحلية بالتطبيق علي صناعة الواح الطاقة الشمسية Policies and mechanisms to deepen Egypt's electronic industries in the light of international experiences with an evaluation of local practices relating to the solar panels industry - د. احمد رشاد الشربيني ، د. اسماء مليجي ربيع، أ. احمد ابراهيم غبد الحميد (معهد التخطيط القومي, 2026)
استهدفت الورقة تقييم واقع الصناعات الإلكترونية في مصر، مع التركيز على صناعة ألواح الطاقة الشمسية، وتسليط الضوء على امكانات وآفاق التقدم نحو رفع نسبة المكون المحلي بصناعة ألواح الطاقة الشمسية، وتقديم اقتراحات بالسياسات والإجراءات المطلوبة لتوطين وتعميق هذه الصناعة في مصر. وقد أكدت الورقة على أن الصناعات الإلكترونية في مصر تفتقر للعمق الصناعي والتكنولوجي الذاتي والمحلي، لاعتمادها على التجميع من مكونات وأجزاء مستوردة وغياب التصميم بغرض الإنتاج؛ وهو ما يمثل نوعاً من الاختلال الهيكلي الأساسي في القطاع الصناعي بصفة عامة، وفي نفس الوقت يزيد الاتجاه نحو التبعية التكنولوجية. وفي السياق نفسه أوضحت الورقة اهتمام مصر بالدخول بشكل مباشر في المراحل النهائية لسلسلة القيمة الخاصة بصناعة ألواح الطاقة الشمسية وتحديدًا المرحلة الخامسة والمتعلقة بتجميع مكونات الألواح الشمسية المستوردة بالكامل (دون الاعتماد على القدرات المحلية لتصنيع بعض هذه المكونات) لكون هذه المرحلة تعتمد بشكل كبير على عنصر العمل مقارنة بعنصري رأس المال والتكنولوجيا التي تعتمد عليهما المراحل الأولي لهذه الصناعة بشكل أكبر. وكشفت الورقة عن وجود إمكانات وقدرات مستقبلية لمصر لتعميق تصنيع مكونات الألواح الشمسية بنسبة تتراوح ما بين 75% إلى 80%. وأهم هذه المكونات النماذج/الألواح الكهروضوئية PV Module والغطاء الزجاجي للألواح الشمسية والإطار الألومنيوم المستخدم في تثبيت مكونات اللوح الشمسي، وصندوق التوصيل الذي يربط الخلايا الشمسية معاً لتكوين اللوح الشمسي، والحامل المعدني للنموذج/ اللوح الشمسي، والكابلات والمحولات، أما تصنيع مكون الخلية الشمسية فيصعب اجتياز المواصفات الفنية الخاصة به، كما يحتاج نقل وتوطين التكنولوجيا الخاصة به إلى استثمارات مرتفعة. وفى هذا الصدد أبرمت وزارة الانتاج الحربي (شركة بنها للصناعات الالكترونية) مؤخرًا بروتوكول تعاون مع شركة GCL الصينية يستهدف تصنيع هذه الخلايا محليًا في الفترة المقبلة. ويستعان بمكاتب استشارية لإجراء دراسات جدوى في هذا الصدد. كما تطرقت الورقة لدراسة المشاكل والتحديات التي ساهمت وتساهم في تواضع هذه الصناعة والتي يمثل تخطيها فرصة هامة لتوطينها وتعميقها في مصر. بالإضافة إلى دراسة بعض التجارب الدولية الرائدة في مجال توطين وتعميق هذه الصناعة، للتعرف على الشروط والمتطلبات والركائز الأساسية التي اعتمدت عليها هذه الدول في تحقيق نهضتها الصناعية، والوقوف على القواسم المشتركة بهذه التجارب. واختتمت الورقة بتقديم اقتراحات بالسياسات والإجراءات المطلوبة لتوطين وتعميق هذه الصناعة في مصر. كلمات مفتاحية: الصناعات الإلكترونية- الطاقة الشمسية- سياسات التعميق. This paper aimed at assessing the present state of the electronic industries in Egypt, with emphasis on the solar panels industry. The potentials and prospects for raising the local content of this industry are discussed, and appropriate policies and procedures for its localization and deepening are proposed. The paper showed that Egypt’s electronic industries lack domestic industrial and technological depth, as they highly depend on assembling imported components and parts, in addition to the absence of design capabilities. Such challenges lead to structural imbalances in the industrial sector and increase technological dependence. However, the paper clarified Egypt's interest in integrating into the fifth stage of the value chain for solar panels manufacturing, which is related to the assembling of imported solar panel components, as this stage is highly dependent on labor rather than on capital and technology, which characterizes the first stages of the industry’s value chain. Moreover, the paper revealed that there are future potentials and capabilities for deepening the manufacturing of solar panel components by 75% to 80%. These components include PV modules/ panels, the glass cover of the solar panels, the aluminum frame which is used for fixing the panel components, the junction box, the metal holder of the module/ solar panel, and cables and transformers. However, the manufacturing of the solar cell component is still facing some technical and technological challenges and requires huge investments. Consequently, the Ministry of Military Production (Banha Electronics company) has signed an agreement with the Chinese GCL company for localizing the manufacturing of solar cells, and the required feasibility studies will be carried out by appropriate consulting offices. The paper discussed the challenges leading to the weak the performance of the solar panels industry in Egypt. Some international experiences of localizing and deepening solar panels industry were studied, in order to determine conditions, requirements for establishing a successful solar panels industry. Identification of the common success factors in the country experiences studied may enhance Egypt’s efforts to deepen its solar panels industry. Finally, the paper concluded with suggestions of the policies and procedures required for localizing and deepening Egypt’s solar panels industry. Keywords: Electronic Industries, Solar energy- Deepening policies.